Contribution of National Sharia Council Fatwa of Indonesian Council of Ulama (DSN-MUI) in The Islamic Economic Development in Indonesia - Abdurrohman Kasdi (IQTISHADIA, 2018)
This research aims to identify the contribution of fatwa (Islamic instructions of rules) from DSN-MUI in developing the theories and practices of the Islamic economics in Indonesia. The research method used is qualitative, which consists of 116 fatwa DSN-MUI as the main subjects of study. The collected data had been analyzed using content analysis method by creating inimitable and valid data inferences related to its context. The results show that DSN-MUI is the only institution mandated by the law to establish fatwa on Islamic economics and finance, and to provide the provisions of Islamic law toward the Islamic financial institutions in carrying out their activities. Since its establishment in 1998, the roles of DSN-MUI are enormous in laying the foundations of the development of Islamic economics in Indonesia. Until the end of 2017, DSN-MUI has issued 116 fatwa on Islamic economics and finances. Even, DSN-MUI has a very important and strategic role in developing and applying sharia values in the economic field. MUI's important and strategic roles are shown from its position as a pioneer in socialization, internalization, and triggering the Islamic economic growth in Indonesia.